Reflections on the physical culture of a scientist - Sadovnikov N. V., Shipanova E. V., Novichkova T. I. (Relevant lines of scientific research: theory and practice, 2024)
Physical culture can be considered as a battery that absorbs the power of intellect, will, memory, which gives meaning to life, allows you to maintain activity and optimism. Education and physical training lay down the norms of social behavior. The greater the heights of the human mind, the more important is prudence in the activities of a scientist responsible for the fate of civilization.
Keywords: мотивация; лидерство; физическая культура; здоровье; наука; интеллект; science; motivation; health; physical education; ученый; intelligence; leadership; a scientist; sanity; здравомыслие